A textual analysis on family in milk product advertisements for children ages three and above - Gador, Karla Gericka s. (2018)
The research looked into the portrayal of family in five different milk product advertisement for children ages three and above and the social and cultural implications of these portrayals in Philippine TV advertising. Using Roland Barthes? narrative codes, the researcher was able to identify the codes used in the five milk product advertisements. Findings showed that advertisements for milk products are mostly grounded on the traditional, conservative image of family and that most families portrayed in the ads are from the middle class. Also, most mothers are stay-at-home, except for one and most fathers are not seen in any part of the ad, except for one. Factors such as, kind of family, gestures, dialogue, and facial expressions were observed in this study. On the five advertisements analyzed in this research, four portrayed a traditional family while one portrayed a non-traditional family. The families were also observed to be practicing Filipino culture, values and belief on family, especially evident in the ads is the Filipino practice of assigning roles to be taken by members of the family.